APOSTLE PAUL'S PRINCIPLES AS A SHEPHERD-TEACHER IN CHRISTIAN RELIGIOUS EDUCATION - SUPIYANI, SUPIYANI (Postgraduate School, Universitas Nusa Cendana, 2022)
Christian Religious Education Teachers are God's co-workers or an important part in carrying out the Great Commission of the Lord Jesus. Paul's principle as a teacher-shepherd is very important in his ministry as a Christian Religious Education teacher in schools. This research is included in the library research category. The researcher compared several reading sources, including the Bible, and concluded the principles of the Apostle Paul as a teacher and a shepherd. Based on the research results, it is concluded that there is a qualitative significance between Paul's principles as the Pastoral Teacher and the Christian Religious Education teacher at school.